STRATEGI PEMASARAN KERIPIK TEMPE SANAN DI KOTA MALANG BERDASARKAN METODE ANALYTICAL HIERARCHY PROCESS (AHP) (Jurnal Sosial Ekonomi Pertanian, 2020)
A good marketing strategy needs to be applied in Tempe chips business. The purpose of this investigation is how the business description Tempe chips business & determine an effective marketing strategy based on the Analytical Hierarchy Process (AHP) business criteria on costs, sales value and profits. This method utilized a random sampling method with several samples studied by 23 industries. Analytical Hierarchy Process (AHP) is applied to determine between alternative kiosk strategies and consignment. The result showed that the more effective strategy was using its kiosk. Analytical Hierarchy Process analysis results produce a value of less than 1, means that the effect of CR
Keywords: UKM; Marketing Strategy; Analytical Hierarchy Process.